A Game-Based Tool for Reducing Jargon Use by Medical Trainees - Emily Burney; Megha Arora; Mizan Gaillard; Maya Herzig; Leo Lester; Su Park; Cliff Coleman (Association of American Medical Colleges, 2024)
Introduction Physicians can be unaware that many US adults have intermediate or lower health literacy. Avoiding medical jargon in patient communication can improve poor outcomes associated with lower health literacy, but physicians may struggle to do so as health literacy education is neither standardized nor universal at US allopathic medical schools. As with other skills-based proficiencies in medical education, repeat exposure and active learning help build competency. Medical students developed the Patient Communication Challenge (PCC), an adaptation of the Hasbro game Taboo, to facilitate practice of patient-centered communication skills among medical trainees. Methods Hour-long workshops were held for groups of preclinical medical students. Students watched a communication exemplar video, played the PCC game, and completed a postworkshop survey. To play, two teams competed to earn points by identifying medical concepts as explained by a teammate who described the term without using medical jargon. Results Evaluations indicated that the game was enjoyable and reinforced didactic concepts through active learning, with self-reported participant satisfaction and competency gain. Overall, 59% of participants (53 of 90) completed postworkshop surveys; 91% (48 of 53) agreed they felt more proficient in avoiding jargon, 94% (50 of 53) would recommend the workshop to a classmate, and 100% (53 of 53) would play again. Discussion The PCC can help early medical trainees develop health communication skills through gamification with utilization of adult learning principles and adequate frequency for skill retention. Future applications include longitudinal assessment and expanding to later stages of medical training and other health professions.